Mathematical dependence for the 137Cs concentration in spent nuclear fuel and its using for experimental data processing - V. V Galchenko; V. L. Diemokhin (Ядерна фізика та енергетика)
The 137Cs behavior during burn up for VVER and RBMK fuel were analyzing. Mathematical dependence for the 137Cs concentration from fuel burn up in the form of is obtained. The formula’s calculation results on 137Cs concentration were compared with ORIGEN and STURBUCS of SCALE-5 computer codes system calculations with some RBMK-1000 fuel experimental data. Using offered dependence the RBMK experimental samples cooling time were founded and isotopic compositions calculations were made with proper cooling time. Difference on some isotopes between calculation and experimental data were reducing.